The Focalization in the Novel “Qawa’ied AlIsiq Al-Arba’oun” the forty rules of love - Hassouni Al Sharifi, Ali; Abdul Hassan Ali, Iman (International Journal of Psychosocial Rehabilitation, 2020)
The narrative presentation mechanisms vary, in addition to the techniques which is used to communicate it to the recipient, these techniques were simple at the beginning of the creation of literary genres, including the novel, but it evolved with the development of life, the writer’s culture and thought, the recipient who focuses on the novel "The Rules of the Forty Love" writer finds Elif Shafak. The writer has excelled in diversifying her writing methods in most of her novels, including the narration of the forty rules of love that are the subject of our study, the recipient finds that the focus technique and narrative vision of the novel were among the most important characteristics of it, to multiply the characters of the novel and its diversity intellectually and socially, in addition to the structure in which the novel is distinguished by the fact that it contained two parallel narrations within it and the author presented it alternately between the novel that was defeated by Ella in the modern era and the novel championed by Shams Al-Din Tabrizi in the ancient era, as this diversity in time and characters made the narrative focus technique a creative medium that contributed to bringing the audience’s attention and influence it, as well as , it is an addition to the events and an artistic beauty of the novel, we found at the end of the study after examining the most important manifestations of the narrative focus and its types that the writer succeeded in employing this technique and made it a great way to present events, we also found that it used most types of narrative focus in it for intellectual and aesthetic purposes.